Lethal and Repellent Effect of the Monoterpene Geraniol on Triatoma infestans Nymphs Susceptible and Resistant to Deltamethrin - Rodas, Carla; Daniele, Martin; Difiori, Naomi Simon; Marin, Gustavo; Schinella, Guillermo; Rodríguez-Vivas, Roger Iván; Dadé, Martín (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Triatoma infestans is the main vector of the Trypanosoma cruzi parasite, the etiological agent of Chagas disease. Pyrethroid insecticides are the most effective strategy for controlling T. infestans. However, the presence of specimens of T. infestans resistant to pyrethroids now raises the need to seek new alternatives for their control. Bioinsecticides are currently positioned as a novel alternative, less aggressive for the environment and less costly compared to traditional synthetic insecticides. Geraniol is a monoterpene that has been shown to have insecticidal and repellent activity on insects. The objectives of this work were to determine and compare the lethal and repellent activity of geraniol alone and in combination with the pyrethroid insecticide deltamethrin and the insect repellent N,N-Diethyl-meta-toluamide (DEET). Geraniol has been shown to be similar lethal to pyrethroid-susceptible and -resistant nymphs (resistance ratio of 0.8). When the two insecticides were combined, geraniol showed a synergistic effect on the lethality of deltamethrin. In terms of repellent activity, geraniol was less effective than DEET at low concentrations; however, when both molecules were combined, the presence of this monoterpene increased the repellency capacity of DEET to 100%. It is concluded that geraniol has lethal activity on T. infestans nymphs susceptible and resistant to pyrethroids and has a synergistic effect on the lethality of deltamethrin. Likewise, geraniol increased the repellency capacity of DEET on T. infestans.